Effect of whole body parameters on knee joint biomechanics: Implications for ACL injury prevention during single-leg landings - Sadeqi, S.; Norte, G. E.; Murray, A.; Erbulut, D. U.; Goel, V. K. (The American Journal of Sports Medicine, 2023)
Background: Previous studies have examined the effect of whole body (WB) parameters on anterior cruciate ligament (ACL) strain and loads, as well as knee joint kinetics and kinematics. However, articular cartilage damage occurs in relation to ACL failure, and the effect of WB parameters on ACL strain and articular cartilage biomechanics during dynamic tasks is unclear.